2016
DOI: 10.2215/cjn.02390316
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Protein Carbamylation and Mortality Risk after Initiation of Hemodialysis

Abstract: Protein carbamylation decreased with dialysis initiation, and a greater reduction over time was associated with a lower risk for mortality. Carbamylation changes were able to predict individuals' mortality risk beyond traditional variables, including markers of dialysis adequacy and nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
2
22
0
2
Order By: Relevance
“…Protein carbamylation , a post translational change due to urea and cyanate exposure, increases in uremia and declines with dialysis. Carbamylated albumin levels fell less in 122 HD patients who died 90–365 days after starting dialysis than it did in 244 matched control patients surviving at least a year . These two groups did not differ in blood urea, Kt / V , normalized protein intake, baseline albumin or carbamylated albumin levels.…”
mentioning
confidence: 82%
“…Protein carbamylation , a post translational change due to urea and cyanate exposure, increases in uremia and declines with dialysis. Carbamylated albumin levels fell less in 122 HD patients who died 90–365 days after starting dialysis than it did in 244 matched control patients surviving at least a year . These two groups did not differ in blood urea, Kt / V , normalized protein intake, baseline albumin or carbamylated albumin levels.…”
mentioning
confidence: 82%
“…For those who had a hemodialysis vintage of < 3 months at baseline ( n = 2), we used blood tests collected three months after hemodialysis initiation. This approach was based on the fact that laboratory variables might be unstable in the first few months after hemodialysis initiation, as previously reported [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, in contemporary dialysis, we’ve found adequacy measures often fail to demonstrate a mortality association as most patients meet minimum recommendations and, unfortunately, doses beyond these requirements have failed to show significant survival benefit nor improvement in uremic toxin clearance [4649]. In this context, we have shown that carbamylation levels are indeed stronger predictors of mortality in ESRD patients on hemodialysis than the conventional urea kinetic based markers [7, 50]. Such findings reiterate that carbamylation should not be considered a simple urea equivalent, rather its levels likely integrate multiple pathologic pathways including nutritional status, inflammation, and time averaged solute clearance and accumulation, making it a potent assessment of health risk.…”
Section: Introductionmentioning
confidence: 99%